Evaluation of canonical correlations between masticatory muscle orientation and craniodentofacial morphology in 10-17 year-olds - Zand, Vahid; Oshagh, Morteza; Iraji Nasrabadi, Nariman; Kharazi, Parvin; Bahramnia, Fatemeh (Journal of Dental School, 2019)
Objectives Different theories have been suggested to define factors involved in skeletal and craniofacial morphology. Many of these theories explain that the bone morphology is the result of the bone tissue capability to adapt in response to biomechanical forces exerted during growth. Also, it seems logical to hypothesize that there is a relationship between biomechanical connections of muscles to bones with the morphology of musculodentoskeletofacial complex. A few studies have evaluated muscle orientation in different skeletal occlusions (class I, II and III). The aim of this study was to evaluate correlations between masticatory muscle orientation and craniodentofacial morphology in different skeletal malocclusions. Materials and Methods A total of 160 lateral cephalograms of patients between 10–17 years in a dental clinic were evaluated for the orientation of masticatory muscles and craniofacial morphology. All cephalograms were traced and confirmed by an orthodontist. Thirty- seven parameters (skeletal, dental, muscular) were measured. For statistical analysis, canonical correlation, variation and linear regression analysis were performed. Results Increase of the masseter muscle angulation was accompanied by a more superior position of the muscle in female subjects with Class II malocclusion. Increase of temporalis muscle angulation was seen in long face males. Increase of the masseter muscle angulation and its higher position were seen in short face males. Conclusion Increase of the masseter muscle angulation was accompanied by a more superior position of the muscle in female patients with class II properties. Increase of temporalis muscle angulation was seen in male patients with long face characteristics. Increase of the masseter muscle angulation and its higher position were seen in male patients with short face properties.